2023
DOI: 10.3390/w15030455
|View full text |Cite
|
Sign up to set email alerts
|

Green Zinc Oxide (ZnO) Nanoparticle Synthesis Using Mangrove Leaf Extract from Avicenna marina: Properties and Application for the Removal of Toxic Metal Ions (Cd2+ and Pb2+)

Abstract: This work used a variety of experimental studies to explore the elimination of cadmium and lead ions from aqueous solutions using a novel method for the biosynthesis of nanoparticles of zinc oxide sorbents (ZnO-NPs) from mangrove leaf extract. The influences of important factors affecting the adsorption technique were determined, including the pH value, contact duration, the initial concentration of metal ions, nano-adsorbent dose, different temperatures, and interfering ions. To confirm the formation of synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…The primary adsorption mechanism was determined further using the Langmuir, Freundlich, Harkin-Jura, Halsey, Redlich-Peterson, and Jovanovic isotherm models. Comparing the obtained goodness-of-fit values for the Langmuir and Freundlich models, the experimental data as presented in Figure 5a,b show the adsorption of E. coli onto the NC surface well described by the Langmuir adsorption isotherm (R 2 = 0.9901) compared to the Freundlich model (R 2 = 0.9399), suggesting majorly the existence of a homogeneous adsorption processes [54]. Thus, the adsorption results generated from this study suggested that the adsorption process predominantly occurs homogeneously at the surface sites of TM@ZnO/TMC NC hydrogel and that the adsorption of E. coli may be assumed to be of monolayer coverage [42].…”
Section: Studies Of Adsorption Isothermmentioning
confidence: 83%
“…The primary adsorption mechanism was determined further using the Langmuir, Freundlich, Harkin-Jura, Halsey, Redlich-Peterson, and Jovanovic isotherm models. Comparing the obtained goodness-of-fit values for the Langmuir and Freundlich models, the experimental data as presented in Figure 5a,b show the adsorption of E. coli onto the NC surface well described by the Langmuir adsorption isotherm (R 2 = 0.9901) compared to the Freundlich model (R 2 = 0.9399), suggesting majorly the existence of a homogeneous adsorption processes [54]. Thus, the adsorption results generated from this study suggested that the adsorption process predominantly occurs homogeneously at the surface sites of TM@ZnO/TMC NC hydrogel and that the adsorption of E. coli may be assumed to be of monolayer coverage [42].…”
Section: Studies Of Adsorption Isothermmentioning
confidence: 83%
“…The green synthesis of ZnONPs was first confirmed via UV–visible spectroscopic analysis, which showed an absorption peak at 370 nm ( Figure 1 a). The absorption peak at this range could be explained by the intrinsic band-gap absorption of ZnO, possibly from the electron exchange from the valence band to the conduction band [ 69 , 71 ]. The ZnONP colloidal solution stability was assessed using the zeta potential based on the charge of fabricated nanoparticles [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neem ( Azadirachta indica ) and tulsi ( Ocimum tenuiflorum ) extracts yielded oval-shaped ZnO NPs with sizes of 100 nm and 122 nm, respectively ( Ajayan and Hebsur, 2020 ). A mangrove leaf extract was used to synthesize spherical ZnO NPs with a size of ∼30 nm ( Al-Mur, 2023 ). Using Costus pictus D. extract, ZnO NPs with tailored size and morphology were fabricated (hexagonal and rod shapes with a reported size of 29 nm) ( Suresh et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%